2014
DOI: 10.1016/j.egypro.2014.11.497
|View full text |Cite
|
Sign up to set email alerts
|

The use of polymer-gel solutions for remediation of potential CO2 leakage from storage reservoirs

Abstract: A polymer-gel based on Polyacylamide with Chromium as cross-linker was used and studied in order to ascertain its rheological characteristics at various concentrations of polymer over a range of temperatures and salinities representative of the subsurface conditions. Core flood experiments were carried out on a high permeability sandstone and fractured marble core samples to investigate the flow characteristics of the polymer-gel in porous/fractured media. Laboratory core-floods revealed significant reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 22 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…In recent years, this technology has been gradually studied in CO 2 conformance control and leakage remediation. To treat the CO 2 leakage problems, the polymer gel system can be injected into the leakage point either through an existing well or a new well that drills through the leakage location. , Gel injection technology as flow diversion and leakage remediation options in CO 2 storage using numerical simulations has been systematically investigated by Wasch et al, Mosleh et al, and Pizzocolo et al Through their research, they found that the repair of the polymer gel plugging layer would form a new diversion, thereby reducing the accumulation of CO 2 leaking into shallow aquifers.…”
Section: Sealant Materials For Co2 Leakage Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, this technology has been gradually studied in CO 2 conformance control and leakage remediation. To treat the CO 2 leakage problems, the polymer gel system can be injected into the leakage point either through an existing well or a new well that drills through the leakage location. , Gel injection technology as flow diversion and leakage remediation options in CO 2 storage using numerical simulations has been systematically investigated by Wasch et al, Mosleh et al, and Pizzocolo et al Through their research, they found that the repair of the polymer gel plugging layer would form a new diversion, thereby reducing the accumulation of CO 2 leaking into shallow aquifers.…”
Section: Sealant Materials For Co2 Leakage Controlmentioning
confidence: 99%
“…Syed et al studied the CO 2 permeability reducing the performance of a PAM-based polymer gel system composed of HPAM and chromium­(III) acetate. Results showed that this polymer gel could reduce the relative permeability to CO 2 by more than 99% in brine (salinity 60,000 mg/L) saturated sandstone cores.…”
Section: Sealant Materials For Co2 Leakage Controlmentioning
confidence: 99%
“…The process to prepare, test, and use a polymer-gel solution to reduce the permeability of porous media has been studied by numerous researchers for various purposes, including remediation of CO 2 leakage from storage reservoirs (Syed et al, 2014) and water shut-off (Bai et al, 2015a) in particular. The workflow in Figure 5 illustrates the approach adopted in this study to broadly investigate the effects of various parameters on gel properties and the performance of the polymer-gel system to block pore space of a range of porous media with varying porosity and permeability.…”
Section: Workflowmentioning
confidence: 99%
“…With regards to the technical issues associated with the CO 2 ‐WAG process, augmented WAG and foam‐assisted WAG have been proposed to improve mobility ratio and reduce the oil/water interfacial tension (IFT) by introducing modifiers such as water‐swelling gels or CO 2 ‐thickening additives. These modifications as a whole are physically strengthened methods performed directly from either water phase plugger or CO 2 phase tackifiers . While from the point of application, oilfield conditions are relatively harsh for these traditional physical modifiers to stably take effect at a given temperature, acidity, and salinity .…”
Section: Introductionmentioning
confidence: 99%